Agricultural investment for growth and poverty reduction in Nigeria - Alpuerto, Vida; Diao, Xinshen; Salau, Sheu; Nwafor, Manson (International Food Policy Research Institute, 2010)
The Comprehensive Africa Agriculture Development Program (CAADP) includes a target of 6 percent annual agricultural growth, supported by the allocation of at least 10 percent of the national budget for agriculture. The Nigerian government has set a higher growth target of 10 percent annual agricultural growth in the medium term, since the country has already achieved the 6 percent target. To achieve such rapid agricultural growth in the next eight years (until 2017), improvements in factor productivity beyond land expansion may be needed, as well as increases in public spending to support the process. This brief assesses the amount, growth, and efficiency of public spending required for Nigeria to reach the agricultural growth target it has established in order to achieve the first Millennium Development Goal (MDG1) of poverty reduction.